INTERRELATIONSHIP BETWEEN FOOD, MEDICINE AND HEALTH AS REFLECTED IN THE ANCIENT TAMIL SOCIETY - M., Suresh; M., Ramakrishnan (International Journal of Research -GRANTHAALAYAH, 2024)
Disease has been a persistent challenge throughout human history, shaping societies’ efforts to understand and address its causes and implications. Advances in cognitive development have improved understanding of diseases and their impacts, yet the complexity of human health persists, rendering complete eradication elusive. Notably, human activities, dietary shifts, and environmental changes have contributed to the emergence of lifestyle-related and human-made diseases. The global rise in chronic diseases underscores the significance of integrating health-promoting foods with medicinal properties into daily life. The concept of "food as medicine" highlights the dual role of certain foods in nutrition and disease prevention, particularly in combating chronic conditions like obesity, diabetes, and heart disease. Regional variations in food-medicine knowledge—shaped by culture, environment, and historical practices—pose challenges for universal application. To bridge these gaps, cross-cultural studies of historical food practices are essential. Traditional medical systems, such as Ayurveda, and ancient texts like Tirukkural, offer valuable insights into dietary health. For instance, Tirukkural’s chapter on medicine provides early recognition of deficiency diseases, aligning with modern classifications of diseases, and emphasizes a logical progression in understanding health. The recent pandemic has further underscored the role of diet in managing and preventing diseases. Medically tailored meals, designed by experts, exemplify the integration of culinary medicine and evidence-based nutrition. This approach complements conventional medicine by addressing dietary complexities, enhancing patient outcomes, and reducing hospitalization rates. The growing emphasis on food as a complementary aspect of healthcare reflects its critical role in global health strategies and policymaking. By uniting traditional wisdom with modern science, the path toward a healthier, disease-resilient society becomes more attainable.